Kajian Psikolinguistik terhadap Gangguan Berbahasa pada Penderita Cadel Melalui Platform YouTube dan TikTok - Devi Bunga Anggreani; Muhammad Rafli Chudori; Sundawati Tisnasari (Pusat riset dan Inovasi Nasional, 2025)
The purpose of this research is to study the phenomenon of slurred language disorder using a psycholinguistic approach. This study concentrates on the phoneme changes that occur in individuals with lisp disorder who are active on digital platforms such as YouTube and TikTok. One definition of lisp disorder is difficulty articulating certain phonemes, especially /r/, /k/, and /s/, which impacts the ability to speak effectively. Using observation and analysis of the utterances of five individuals with a lisp featured in the videos, this study employed a descriptive qualitative methodology for data collection. Based on the age and physical condition of each subject, the analysis results show the substitution of the phonemes /r/ into /l/, /w/, /g/, /c/, /k/ into /t/, and /s/ into /c/. This study provides important knowledge about the phonological changes of lisp disorder and how it impacts language acquisition and public communication in the digital age.